2016
DOI: 10.1097/acm.0000000000001093
|View full text |Cite
|
Sign up to set email alerts
|

Professional Formation in the Gross Anatomy Lab and Narrative Medicine: An Exploration

Abstract: As an early and important experience in medical education, dissection in the gross anatomy lab is a locus of professional formation. Because students often think of their professional development in evolving, narrative terms, the authors propose that close attention to these narratives might add to understanding of professional formation in progress. They solicited written reflections from students, to explore ways that both the content and form of written reflections might illuminate themes relevant to profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 13 publications
1
22
0
2
Order By: Relevance
“…We observed that the stated goals of NM programmes were not always reflective of the reported evaluation outcomes. Programmes identified a variety of goals, but a striking number did not report actual evaluation results (n=14)34 35 53 54 56 59–62 75 79 80 83 92 or only discussed general participant satisfaction (n=7) 51 58 69 71 72 89 91. We found the evaluation methods and outcomes of many programmes to be insufficiently developed or described.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…We observed that the stated goals of NM programmes were not always reflective of the reported evaluation outcomes. Programmes identified a variety of goals, but a striking number did not report actual evaluation results (n=14)34 35 53 54 56 59–62 75 79 80 83 92 or only discussed general participant satisfaction (n=7) 51 58 69 71 72 89 91. We found the evaluation methods and outcomes of many programmes to be insufficiently developed or described.…”
Section: Resultsmentioning
confidence: 91%
“…During the second screening stage, we read the full texts of records, identifying a further 109 records to exclude due to our discovering on full-text review that they did not meet our established eligibility criteria (figure 1). Following the full-text screening, 61 records qualified for review 15 22 33–89. However, we discovered that several qualifying records addressed identical NM programming efforts at the same institution: that is, 12 records15 22 41 42 44–48 52 70 84 represented 6 programmes.…”
Section: Methodsmentioning
confidence: 99%
“…One, by Shiozawa and colleagues, describe a professionalism seminar that ran concurrently with the anatomy course 61 . A second, by Kissler and colleagues, introduced written reflections on professional themes as part of the anatomy course 62 . Overall, these studies provide some evidence that the anatomy laboratory experience contributes to the development of professional attitudes.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical Anatomy published a special issue on professionalism and anatomy in 2006 (Pawlina, ), and in 2016 published a special issue on ethics (Tubbs, ). Over the past two decades, many researchers have studied the roles and responsibilities of anatomy faculty, anatomy laboratory content, and laboratory learning processes in developing professional, ethical, caring health care providers for the future (Dyer and Thorndike, ; Escobar‐Poni and Poni, ; Lachman and Pawlina, ; Swartz, ; Swick, ; Moore and Benninger, ; Kissler et al, ; Rehkämper, ). According to Swartz (), the anatomy laboratory is rich with opportunities for fostering student growth in both scientific knowledge acquisition and professional attitudes toward patient care including the importance of accountability, collaboration, respect, and social responsibility.…”
Section: Introductionmentioning
confidence: 99%